2011
DOI: 10.1002/jcla.20456
|View full text |Cite
|
Sign up to set email alerts
|

p-cresylsulfate and indoxyl sulfate level at different stages of chronic kidney disease

Abstract: Indoxyl sulfate and p-cresylsulfate was associated with poor clinical outcome of uremia. We explored the relationship between the two toxins and renal function in chronic kidney disease (CKD) patients. This study enrolled 103 stable CKD patients (stage 3-5 and hemodialysis (HD) patients). Serum levels of indoxyl sulfate and p-cresylsulfate were measured using ultra performance liquid chromatography. General laboratory results and patient background were also checked. Patients with advanced CKD had higher serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 25 publications
1
95
2
1
Order By: Relevance
“…Of importance, the PCS concentration after administration was in the range of levels observed in patients with ESRD. 10,39 The ectopic lipid redistribution and reduction of fat accretion in PCS-treated mice were the result of a direct effect of PCS treatment rather than malnutrition because food intake and body weight were not altered. Fat mass loss should be related to the fact that we observed a decrease in the volume of adipocytes, which may reflect adipocyte dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Of importance, the PCS concentration after administration was in the range of levels observed in patients with ESRD. 10,39 The ectopic lipid redistribution and reduction of fat accretion in PCS-treated mice were the result of a direct effect of PCS treatment rather than malnutrition because food intake and body weight were not altered. Fat mass loss should be related to the fact that we observed a decrease in the volume of adipocytes, which may reflect adipocyte dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…106 Concentrations of indoxyl sulfate and p-cresyl sulfate in the serum are negatively correlated with the level of kidney function. 12 A prospective, observational study performed in 268 patients with CKD indicated that baseline levels of indoxyl sulfate and p-cresyl sulfate were predictors of CKD progression. 13 Animal studies suggest that these uremic toxins may damage renal tubular cells.…”
Section: Intestinal Dysbiosis In Ckd/ Esrdmentioning
confidence: 99%
“…[9][10][11] Preliminary evidence indicates that toxic products generated by a dysbiotic gut microbiome may contribute to progression to CKD and CKD-related complications ( Figure 1). 12,13 GUT MICROBIOTA: AN …”
mentioning
confidence: 99%
“…Protein-derived tryptophan is metabolized into indole, which is then absorbed into the bloodstream and oxidized into indoxyl sulfate (IS) in the liver (6). IS is normally excreted into the urine, but patients with CKD cannot effectively excrete IS because of reduced renal function (7,8). Elevated serum IS causes elevated expression of genes related to tubulointerstitial fibrosis, such as those coding for TGF-b1 and collagen (9,10).…”
Section: Introductionmentioning
confidence: 99%